Geopolitical Disruption and Supply Chain Resilience: The Impact of the Iran–US–Israel Conflict on Indonesia's Plastic Naphtha Crisis - Muhamad Agung Dharmajaya; Eva Sutihat; Nono Arief Rachman; Masitoh Masitoh (Politeknik Siber Cerdika Internasional, 2026)
Background: The escalation of armed conflict between Iran, the United States, and Israel since February 2026 has triggered massive disruptions in global supply chains, acutely manifesting in a naphtha crisis, the primary raw material for the plastic packaging industry. As a country that imports approximately 60–70% of its naphtha requirements from the Middle East, Indonesia faces extreme price volatility and supply uncertainty that threatens national manufacturing stability. Objective: This study aims to analyze the impact of such geopolitical disruptions on the supply chain resilience of the plastic packaging industry in Indonesia, focusing on crisis transmission through the naphtha supply route. Methods: The research methodology employed a qualitative case study approach through document analysis, in-depth interviews with industry stakeholders, and a comprehensive literature review. Results: Key findings indicate that companies implementing dynamic capabilities, specifically in the aspects of sensing, seizing, and reconfiguring, have demonstrated stronger and more adaptive mitigation responses compared to companies relying on a single sourcing strategy. The discussion highlights that operational flexibility and supplier diversification are critical determinants in maintaining production continuity. Conclusion: This study highlights the importance of developing an adaptive geopolitical supply chain resilience framework for manufacturing industries in developing countries that have a high dependency on imported energy commodities.